The explanation of muwālāt in Zuhaily’s exegesis “al Tafsir al munir” - Iman Kanani; Muhammad Zarasi; Zulkifli Mohd Yusoff (UIN Sunan Gunung Djati Bandung, 2016)
One of the crucial contemporary issues of Islamic thought that has brought complicated situation in Muslims states, on the one hand, and between Muslims and non-Muslims on the other hand, is the issue of muwālāt. The literal understanding of muwālāt has caused profound problems in human societies, especially in the multi-religion countries. This research clarifies the meaning of loyalty in the Qur’ān based on al-Zuḥayli’s exegesis by using analytical -inductive method. The present study also elucidates Al-Zuḥayli’s point of view towards spiritual muwālāt and humane social muwālāt in the Quran.Hence, the study reveals fruitful findings and output, indicating that al-Zuḥayli separated muwālāt to three categories; prohibited muwālāt, muwālāt that causes infidelity, and muwālāt which means nice cohabitation with others. Also, the study explores that al-Zuḥayli believes that the principle in relations with Non-Muslims is based on peace. Furtheremore, al-Zuḥayli pointed out that muwālāt is permissible when it benefits Muslim society and Non- Muslim are not fighting with or betraying Muslims. Also the study presents that al-Zuḥayli has distinguished between muwālāt that means monotheism and worshiping God, and other types of muwālāt.